Barbie on Social Media: The Success of a Campaign Beyond the Cinema and the Box Office - Bustos Díaz, Javier; Perelló Sobrepere, Marc; Martín-Vicario, Lara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The success of the premiere of the film Barbie is undeniable in terms of box office and social impact; however, another of the aspects in which the film stands out is its impact in terms of communication and promotion. The aim of this paper is to analyse the impact that the official Barbie account had on social networks during the week of the premiere. To achieve this objective, a quantitative methodology based on the Fanpage Karma social network analysis tools was used. Among the main results, it is worth highlighting that TikTok emerges as the communication and marketing channel that generates the most engagement, to the detriment of Facebook and Twitter (X).